2013
DOI: 10.1002/smll.201301111
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle‐Programmed Self‐Destructive Neural Stem Cells for Glioblastoma Targeting and Therapy

Abstract: A 3‐step glioblastoma‐tropic delivery and therapy method using nanoparticle programmed self‐destructive neural stem cells (NSCs) is demonstrated in vivo: 1) FDA‐approved NSCs for clinical trials are loaded with pH‐sensitive MSN‐Dox; 2) the nanoparticle conjugates provide a delayed drug‐releasing mechanism and allow for NSC migration towards a distant tumor site; 3) NSCs eventually undergo cell death and release impregnated MSN‐Dox, which subsequently induces toxicity towards surrounding glioma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 29 publications
2
84
0
Order By: Relevance
“…MIAMI cell-mediated delivery may also result in better Fc-diOH retention within the tumor environment, constituting another advantage of this cell delivery system over LNCs alone. Consistent with our results, Cheng et al 38 recently reported that intratumoral and contralateral injections of a neural stem cell line loaded with doxorubicin (Dox)-mesoporous silica nanoparticles elicited a significantly stronger therapeutic effect than Doxmesoporous silica nanoparticles alone in the U87MG GB model. Dox was found to be widely distributed specifically within the tumor following the use of this neural stem cell line carrier.…”
Section: Discussionsupporting
confidence: 93%
“…MIAMI cell-mediated delivery may also result in better Fc-diOH retention within the tumor environment, constituting another advantage of this cell delivery system over LNCs alone. Consistent with our results, Cheng et al 38 recently reported that intratumoral and contralateral injections of a neural stem cell line loaded with doxorubicin (Dox)-mesoporous silica nanoparticles elicited a significantly stronger therapeutic effect than Doxmesoporous silica nanoparticles alone in the U87MG GB model. Dox was found to be widely distributed specifically within the tumor following the use of this neural stem cell line carrier.…”
Section: Discussionsupporting
confidence: 93%
“…For this approach, a nano-scaled drug delivery system (e.g. functionalized nanoparticles [41]) allowing for [I-125]ITdU to be efficiently transported across the BBB for targeting of GSC could be a solution.…”
Section: Discussionmentioning
confidence: 99%
“…155 Nanoparticles have also been used for cell tracking. NSC loaded with iron oxide nanoparticles can be transplanted and subsequently tracked using noninvasive magnetic resonance imaging.…”
Section: Advances In Polymer Chemistry and Nanoparticle Delivery For mentioning
confidence: 99%